Democracy promotion and Western aid to Africa: Lessons from Ethiopia (1991-2012) - Teshome, Wondwosen (Journal of Human Sciences, 2013)
Since the end of the Cold War, Western donors have been following a strategy of democracy promotion to Africa that involves giving assistance to both the state and the non-state actors including governments (as part of good governance program), parliaments, courts, political parties, civil society, electoral management bodies, election observation missions etc. The paper explores both the positive and the negative impacts of such assistance to African emerging democracies by using Ethiopia as a case study. The paper primarily deals with three sub-sectors of democracy promotion program: assistances to political parties, international election observation missions, and civil society. In this study, I argue that human rights and self interest (economic, political or both) shape the foreign aid policy of Western donors including democracy assistance. Moreover, the paper attempts to prove that democratic reversals or backsliding and human rights abuses in the recipient states can trigger aid reduction or termination only when the recipient states are neither economically nor strategically valuable to the Western donors.